Off-pump resection of a giant inflamed epicardial cyst - Daisuke Kaneyuki; Tomoki Sakata; Anan Nomura; Manabu Sakurai; Kenji Mogi; Yoshiharu Takahara (Surgical Case Reports)
Abstract Background Epicardial cysts are rarer benign tumors than pericardial cysts. There have been few reports on surgical management for epicardial cysts. Case presentation A 73-year-old woman with dyspnea on exertion had a giant cyst (12 × 10 cm in diameter) on preoperative computed tomography. Compression of the left atrium and ventricle by the cyst was considered to be the cause of her symptoms. The cyst was diagnosed with an epicardial cyst intraoperatively. Although the cyst adhered to surrounding tissues, it was successfully resected with off-pump surgery by using a heart positioner and an ultrasonic scalpel. Conclusions Surgeons should consider off-pump surgery as an alternative to video-assisted thoracoscopic surgery and on-pump surgery for complicated epicardial cysts.